2020
DOI: 10.1007/s00253-020-10350-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches for efficient  in vivo fermentation production of noncoding RNAs

Abstract: Genome-derived noncoding RNAs (ncRNAs), including microRNAs (miRNAs), small interfering RNAs (siRNAs), and long noncoding RNAs (lncRNAs), play an essential role in the control of target gene expression underlying various cellular processes, and dysregulation of ncRNAs is involved in the pathogenesis and progression of various diseases in virtually all species including humans. Understanding ncRNA biology has opened new avenues to develop novel RNA-based therapeutics. Presently, ncRNA research and drug developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 84 publications
0
49
0
Order By: Relevance
“…Our recent efforts have led to the establishment of a novel platform to produce recombinant or bioengineered miRNA molecules for miRNA replacement therapy ( Wang et al, 2015 ; Jilek et al, 2019 ; Tu et al, 2019 ). Different from chemo-engineered RNA agents made in vitro and comprised of extensive and various types of artificial modifications, bioengineered RNA agents are produced and folded in live cells and thus may better recapitulate the structures, biologic functions, and safety profiles of natural RNAs ( Yu et al, 2019 , 2020 ). By using bioengineered miR-1291 agents, the present study established the role of tumor-suppressive miR-1291 in the perturbation of PC cell metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent efforts have led to the establishment of a novel platform to produce recombinant or bioengineered miRNA molecules for miRNA replacement therapy ( Wang et al, 2015 ; Jilek et al, 2019 ; Tu et al, 2019 ). Different from chemo-engineered RNA agents made in vitro and comprised of extensive and various types of artificial modifications, bioengineered RNA agents are produced and folded in live cells and thus may better recapitulate the structures, biologic functions, and safety profiles of natural RNAs ( Yu et al, 2019 , 2020 ). By using bioengineered miR-1291 agents, the present study established the role of tumor-suppressive miR-1291 in the perturbation of PC cell metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, although chemical synthesis and purification can be automated, chemoengineered RNA drugs are among the most expensive medications on the market ( Simoens and Huys, 2017 ; Burgart et al, 2018 ), and the access to large quantities of synthetic RNAs required for animal studies, clinical investigations, and medical use among a large population remains a challenge. There were also concerns about inevitable effects of artificial modifications on RNA folding, activity, and safety as compared with natural RNAs produced and folded in living cells ( Ho and Yu, 2016 ; Yu et al, 2019 , 2020 ). Advances in RNA therapeutics will likely rely on the improvements of design and utilization of proper RNA molecules as well as delivery systems and targeting technologies to ensure efficacy and avoid or minimize off-target effects and immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, post-transcriptional modifications have been shown to suppress immune responses in cells ( Nallagatla et al, 2008 ; Gehrig et al, 2012 ), whereas many chemical modifications induce immunogenicity. Therefore, there are growing interests in developing bioengineering technologies to produce true biological RNA molecules in living cells for research and development ( Ho and Yu, 2016 ; Yu et al, 2019 , 2020 ), similar to protein research and drug development that create and use recombinant or bioengineered proteins.…”
Section: Rnas As Therapeutic Drugsmentioning
confidence: 99%
“…Non-coding RNA (ncRNA) is a class of RNA that is transcribed from DNA but is not translated into a protein, types of ncRNA include small interfering RNA (siRNA), long ncRNA (lncRNA) and microRNA (miRNA) (37,38). A previous study demonstrated that the interaction between HIF-1 and ncRNA is significant in the self-renewal and proliferation of CSCs.…”
Section: Role Of Hif-1 In Non-coding Rna Associated With Cscsmentioning
confidence: 99%